2018
DOI: 10.1515/znb-2018-0121
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of 1,3-diphosphacyclobutadiene cobalt complexes via Si–P bond insertion

Abstract: We report the synthesis of functionalized 1,3-bis(diphosphacyclobutadiene) complexes via the insertion of carbon-oxygen bonds of ethers, esters, aldehydes and amides into the P–Si bond of silylated complexes. Reactions of [K(tol)2][Co(η4-P2C2R2)2] [[K(tol)2][1a]: R=tBu, [K(tol)2][1b]: R=tPent (=tert-pentyl)] with Me3SiCl afford the trimethylsilyl-substituted derivatives [Co(η4-P2C2R2SiMe3)(η4-P2C2R2)] (2a,b, R=tBu, tPent). The Me3Si group is connected to a phosphorus atom of one of the 1,3-diphosphacyclobutadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…As a result, this formerly planar ligand is tilted (P3‐C3‐P4/P4‐C4‐P3 planes 27.9°; the same dihedral angle amounts to 12.5° in endo ‐H‐ 1 and 7.5° in G ), and the Co1−P3 distance (2.4066(5) Å) is significantly elongated compared with Co1−P4 (2.2584(5) Å). In contrast to related trimethylsilated bis(1,3‐diphosphacyclobutadiene) complexes [Co(P 2 C 2 R 2 ) 2 (SiMe 3 )], the Me 3 Si moiety assumes an endo ‐configuration pointing towards the cobalt. This unexpected arrangement might be explained by a template effect of the lithium cation, which assumes a bridging position in the molecular structure of endo ‐H‐ 1 .…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…As a result, this formerly planar ligand is tilted (P3‐C3‐P4/P4‐C4‐P3 planes 27.9°; the same dihedral angle amounts to 12.5° in endo ‐H‐ 1 and 7.5° in G ), and the Co1−P3 distance (2.4066(5) Å) is significantly elongated compared with Co1−P4 (2.2584(5) Å). In contrast to related trimethylsilated bis(1,3‐diphosphacyclobutadiene) complexes [Co(P 2 C 2 R 2 ) 2 (SiMe 3 )], the Me 3 Si moiety assumes an endo ‐configuration pointing towards the cobalt. This unexpected arrangement might be explained by a template effect of the lithium cation, which assumes a bridging position in the molecular structure of endo ‐H‐ 1 .…”
Section: Resultsmentioning
confidence: 89%
“…The stereochemistry is conserved in this reaction. Considering the high reactivity of closely related silylated 1,3‐diphosphacyclobutadiene complexes, a plethora of functionalized sandwich complexes should be accessible by insertion reactions in the phosphorus–silicon bond of such complexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these studies revealed various novel coordination compounds, the desired tris(diphosphacyclobutadiene) tripledecker complex remained elusive. Gratifyingly, subsequent studies using the silylated complex [Co(η 4 -P2C2tBu2SiMe3)(η 4 -P2C2tBu2)] (E) 17 met with success. When the latter species is reacted with [Cp*RhCl2]2 (0.5 equivalents, Scheme 1) in toluene, a brownish green reaction mixture is formed, which contains two species according to 31 P{ 1 H} NMR spectroscopic monitoring: The known sandwich compound [Cp*Rh(η 4 -P2C2tBu2)] (2) 18 can be identified as the major product by a doublet at 39.5 ppm ( 1 JRhP = 27 Hz) and 1 as the minor product by a set of two singlets at δ = 55.7 and 111.1 ppm in a 2:1 ratio.…”
mentioning
confidence: 99%
“…Although these studies revealed various novel coordination compounds, the desired tris(diphosphacyclobutadiene) tripledecker complex remained inaccessible. Gratifyingly, subsequent studies using the silylated complex [Co(η 4 -P 2 C 2 t Bu 2 SiMe 3 )(η 4 -P 2 C 2 t Bu 2 )] ( E ) 20 met with success (Scheme 1). When the latter species is reacted with [Cp*RhCl 2 ] 2 (0.5 equivalents) in toluene, a brownish green reaction mixture is formed, which contains two species according to 31 P{ 1 H} NMR spectroscopic monitoring: The known sandwich compound [Cp*Rh(η 4 -P 2 C 2 t Bu 2 )] ( 2 ) 21 can be identified as the major product by a doublet at 39.5 ppm ( 1 J RhP = 27 Hz) and 1 as the minor product by a set of two singlets at δ = 55.7 and 111.1 ppm in a 2 : 1 ratio.…”
mentioning
confidence: 99%